CORPUS AND INCOME IN TRUST ACCOUNTING. - Rosbe, Robert L. (The Accounting Review, 1939)
Uses and trusts originated in England shortly after the Norman Conquest. From that time to 1535 there existed two classes of trusts in England, active and passive. Where A conveyed land to B for a period of years instructing B to apply the income of the land for the use of C an active trust was created. If A conveyed land to B who was to hold the land permanently for the benefit of C with no positive duties to be exercised by B a passive trust or use was created. The latter type was far more common than the former. It was used principally to avoid some of the burdens which fell upon the holder of the legal title. Under the feudal system the lord was entitled to a "relief," or payment of money, when land descended to an heir of full age; and to "aids" upon the marriage of a daughter of the lord, the knighting of his eldest son, or when the lord was held for ransom. By conveying the legal title to another and reserving the use to himself the tenant escaped such exactions. An attempt is here made to discuss the treatment of a few items of receipt and disbursement frequently omitted in the provisions of trust instruments. Despite the fact that all the statements made in this paper can be supported by legal authority, not all jurisdictions hold alike in similar circumstances. Furthermore, with changing social conditions, and changing personnel in courts and legislatures, the law of a particular jurisdiction may be quickly modified or completely revised.